The Effect Ofexperimental Methods On Cognitive Capabilities Of Science Concept Education in Early Children Education in the Playground Playing FKIP Unpatti Ambon - Rosmaryn Tutupary; Emma Rumahlewang (International Journal of Education, Information Technology, and Others, 2020)
This study aims to (1) Determine cognitive abilities in early childhood science concepts before being taught with the experimental method of KB Mawar FKIP UNPATTI (2) Knowing cognitive abilities in early childhood science concepts after being taught with the experimental method in KB Mawar FKIP Unpatti Ambon (3) Testing the significant difference in influence between before and after the use of experimental methods on cognitive abilities of early childhood science concepts in KB Mawar FKIP Ambon Ambon. This research was conducted at KB Mawar FKIP Unpatti Ambon. The method used is a quasi-experimental design with one group pretest-posttes. The population of this research was all students of KB Mawar FKIP Unpatti Ambon who were 6 years old. Sampling of this study was carried out using proportional random sampling technique which was carried out randomly in 1 class that is 10 people. Data was collected through an instrument of observation of the cognitive abilities of scientific concepts. The reliability of achievement motivation instruments is 0.89, the learning achievement test is 0.87. Data from the results of this study were processed using the t test analysis technique for independent samples at a significance level α = 0.0.